Prediction of drafted-triathlon race time from submaximal laboratory testing in elite triathletes - Hue, O. (Canadian Journal of Applied Physiology, 2003)
PURPOSE AND METHODS: To determine which physiological variables accurately predict the race time of an Olympic-distance International Triathlon undertaken in drafted conditions, 8 elite triathletes underwent both maximal and submaximal laboratory and field physiological testing: a 400-m maximal swim test; an incremental treadmill test; an incremental cycling test; 30 min of cycling followed by 20 min of running (C-R); and 20 min of control running (R) at the exact same speed variations as in running in C-R. Blood samples were drawn to measure venous lactate concentration after the 400-m swim and the cycle and run segments of C-R. During the maximal cycling and running exercises, data were collected using an automated breath-by-breath system. RESULTS: The only parameters correlated with the overall drafted-triathlon time were lactate concentration noted at the end of the cycle segment (r = 0.83, p < 0. 05) and the distance covered during the running part of the submaximal C-R test (r = 0.92, p < 0. 01). Stepwise multiple regression analysis revealed a highly significant (r = 0.96, p < 0.02) relationship between predicted race time (from laboratory measures) and actual race time, using the following calculation: Predicted Triathlon Time (s) = 1.128 (distance covered during R of C-R [m]) + 38.8 ([lactate] at the end of C in C-R) + 13,338. The high R2 value of 0.93 indicated that, taken together, these two laboratory measures could account for 93% of the variance in race times during a drafted triathlon. CONCLUSION: Complementing previous studies, this study demonstrates that different parameters seem to be reliable for predicting performance in drafted vs. nondrafted Olympic-triathlon races. It also demonstrates that, for elite triathletes competing in a drafted Olympic-distance triathlon, performance is accurately predicted from the results of submaximal laboratory measures.